Comparative gene co-expression networks show enrichment of brassinosteroid and vitamin B processes in a seagrass under simulated ocean warming and extreme climatic events - Booth, Mitchell W.; Sinclair, Elizabeth A.; Jung, Elisabeth Maria U.; Austin, Rachel; Bayer, Philipp E.; Krauss, Siegfried L.; Breed, Martin F.; Kendrick, Gary A. (Frontiers in Plant Science, 2024)
Ocean warming combined with extreme climatic events, such as marine heatwaves and flash flooding events, are threatening seagrasses globally. How seagrasses will cope with these challenges is uncertain, particularly for range-edge populations of species like Posidonia australis in Shark Bay, Western Australia. Analysing gene expression while manipulating multiple stressors provides insight into the genetic response and resilience of seagrasses to changing climate. We conducted a gene expression study on a polyploid clone of P. australis during an 18-week mesocosm experiment to assess responses to single and combined future climate change associated stressors. Plants were exposed to (1) future ocean warming temperature (baseline +1.5 °C) followed by a simulated marine heat wave (baseline +5.5 °C), (2) light deprivation simulating observed marine heatwave driven turbidity (95 % shade) at baseline temperatures, or (3) both stressors simultaneously. Basal leaf meristem was sampled for gene expression analysis using RNA-seq at four time points during the experiment. Weighted gene co-expression network analysis, GO term enrichment and KEGG pathway enrichment analyses were used to identify stress responses. Shaded plants showed a specific gene enrichment for shade avoidance (programmed cell-death) after three weeks of stress, and before any heated tanks showed a specific heat-response. Shaded plants were still positively correlated for programmed cell death and stress-related processes at the end of the experiment. Once ocean warming temperatures (+1.5 °C) were in effect, gene enrichment for heat stress (e.g., ROS scavenging and polyamine metabolism related) were present. Vitamin B processes, RNA polymerase II processes and light-related meristematic phase change were expressed with the addition of the simulated MHW. Heated plants showed meristematic growth signatures, as well as trehalose and salicylic acid metabolism. Brassinosteroid related processes were significantly enriched in all stressor treatments at all time points, except for the isolated heat stressed plants after three weeks of stressor initiation. Gene expression responses to the interaction between heat waves and turbidity induced light reduction support observed geographical scale mortality in seagrasses observed for P. australis in Shark Bay and suggest that even this giant polyploid clone will be negatively impacted by more extreme climate change projections.